Varangian in Byzantium. Harald Hardraade's Sicilian adventure - Wolińska, Teresa (Balcanica Posnaniensia. Acta et studia, 2009)
The aim of the article is to present the role of the Varangian commander Harald (later Harald III the Terrible – King of Norway) and his team in the politics and military activities of the Byzantine Empire at the beginning of the 11th century (1034–1042). The author analyses his role in specific political and military events related to Byzantium, from the battles against the Arabs and Pechenegs, through his participation in suppressing Peter Deljan's uprising in Bulgaria, to political conflicts in Constantinople. The analysis is based on Scandinavian sources (sagas, poetry, chronicles), Byzantine sources and Latin chronicles. The conclusions indicate that although the source accounts mix facts with elements of fiction, Harald's presence in Maniakes' army in Sicily is well established. This campaign was the last attempt to recapture the island from the Arabs and was of strategic importance for the restoration of Byzantium's position in Italy. For Harald, his stay in Byzantium proved crucial – it allowed him to gain military fame, political experience and considerable wealth, which he used after his return to Rus' and Norway. The Byzantine episode in Harald Hardrada's life was of fundamental importance for his further career and strengthened his position in both the Nordic and Byzantine traditions.